Decolonizing linguistics - Charity Hudley, Anne H.; Mallinson, Christine; Bucholtz, Mary 1966- (New York, NY Oxford University Press, 2024)
Decolonizing Linguistics, the companion volume to Inclusion in Linguistics, is designed to uncover and intervene in the history and ongoing legacy of colonization and colonial thinking in linguistics and related fields. Taken together, the two volumes are the first comprehensive, action-oriented, book-length discussions of how to advance social justice in all aspects of the discipline.

The introduction to Decolonizing Linguistics theorizes decolonization as the process of centering Black, Native, and Indigenous perspectives, describes the extensive dialogic and collaborative process through which the volume was developed, and lays out key principles for decolonizing linguistic research and teaching. The twenty chapters cover a wide range of languages and linguistic contexts (e.g., Bantu languages, Creoles, Dominican Spanish, Francophone Africa, Zapotec) as well as various disciplines and subfields (applied linguistics, communication, historical linguistics, language documentation and revitalization/reclamation, psycholinguistics, sociolinguistics, syntax).

Contributors address such topics as refusing settler-colonial practices and centering community goals in research on Indigenous languages; decolonizing research partnerships between the Global South and the Global North; and prioritizing Black Diasporic perspectives in linguistics. The volume's conclusion lays out specific actions that linguists can take through research, teaching, and institutional structures to refuse coloniality in linguistics and to move the field toward a decolonized future"--Back cover
Introduction: decolonizing linguistics / Anne H. Charity Hudley, Ignacio L. Montoya, Christine Mallinson, and Mary Bucholtz -- Part 1: Decolonizing linguistics and the academy -- 1. Manifestations of colonialism in linguistics and opportunities for decolonization through refusal / Ignacio L. Montoya -- 2. Racialization, language science, and nineteenth-century anthropometrics / Margaret Thomas -- 3. The colonial geography of linguistics: a view from the Caribbean / Ben Braithwaite and Kristian Ali -- 4. We like the idea of you but not the reality of you: the whole scholar as disruptor of default colonial practices in linguistics / Nicté Fuller Medina -- 5. Apolitical linguistics doesn't exist, and it shouldn't: developing a Black feminist praxis toward political transparency / Aris Moreno Clemons -- 6. Unpacking experiences of racism in European applied linguistics / Kamran Khan -- 7. Centering race and multilingualism in French linguistics / Maya Angela Smith -- 8. Decolonizing (psycho)linguistics means dropping the language gap rhetoric / Megan Figueroa -- Part 2: Decolonizing methods of teaching and research -- 9. From gatekeeping to inclusion in the introductory linguistics curriculum: decolonizing our teaching, our psyches, our institutions, and our field / Lynnette Arnold -- 10. Decolonizing historical linguistics in the classroom and beyond / Claire Bowern and Rikker Dockum -- 11. Towards a decolonial syntax: research, teaching, publishing / Hannah Gibson, Kyle Jerro, Savithry Namboodiripad, and Kristina Riedel -- 12. Decolonising methodologies through collaboration: reflections on partnerships and funding flows from working between the South and the North / Rajendra Chetty, Hannah Gibson, and Colin Reilly -- 13. Open methods: decolonizing (or not) research methods in linguistics / Dan Villarreal and Lauren Collister -- 14. Revitalizing attitudes toward Creole languages / Ariana Bancu, Joy P. G. Peltier, Felicia Bisnath, Danielle Burgess, Sophia Eakins, Wilkinson Daniel Wong Gonzales, Moira Saltzman, Yourdanis Sedarous, Alicia Stevers, and Marlyse Baptista / Part 3: Decolonizing research by centering community and activism -- 15. Solidarity and collectivity in decolonizing linguistics: a Black diasporic perspective / Anne H. Charity Hudley, Christine Mallinson, Kahdeidra Monét Martin, Aris Moreno Clemons, L. J. Randolph Jr., Mary Bucholtz, Kendra Calhoun, Shenika Hankerson, Joy P. G. Peltier, Jamie A. Thomas, Deana Lacy McQuitty, and Kara Seidel -- 16. Growing a bigger linguistics through a Zapotec agenda: the Ticha Project / May Helena Plumb, Alejandra Dubcovsky, Moisés García Guzmán, Brook Danielle Lillehaugen, and Felipe H. Lopez -- 17. Decolonizing Creolistics through popular culture: the case of dancehall / Rashana Vikara Lydner -- 18. Prioritizing community partners' goals in projects to support indigenous language revitalization / Katherine J. Riestenberg, Ally Freemond, Brook Danielle Lillehaugen, and Jonathan N. Washington -- 19. Promoting decolonized classrooms through an introductory linguistics course for future teachers in Alaska / Ève Ryan, Matt Ford, and Giovanna Wilde -- 20. An interdisciplinary approach to language activism from community colleges: linguistics meets communication studies / Carlos de Cuba, Poppy Slocum, and Laura Spinu -- Conclusion: decolonizing linguistics / Anne H. Charity Hudley, Ignacio L. Montoya, Christine Mallinson, and Mary Bucholtz.
Includes bibliographical references.
Keywords: Linguistics -- Study and teaching. -- Social aspects; Language and languages -- Study and teaching -- Social aspects